THE ANALYSIS ON STUDENT’S ABILITY IN SPEAKING OF THE EIGHT GRADE AT SMP SATAP NEGERI SIPI - Naibobe, Eva Maria (LPPM Universitas Mercu Buana Yogyakarta, 2023)
The aims of this research are: to know the level of the student’s speaking ability, to find out the aspect difficult for the student’s in speaking ability. The research method that use in this study was descriptive qualitative method.This research used an oral test with three topics of conversation, as the instrument. The data were recorded by using handphone, after collect the data, the writer analyzed them based on the 4 aspects of speaking ability namely: vocabulary, structure, pronounciation, and fluency. In this research the writer took the data from SMP Satap Negeri Sipi with the sample 25 students in class eight. Based on the data the student’s speaking ability shows that from 25 students, 7 students got excellent with the score 4.00, 16 students got good with the score 3.00 – 3.9, and 2 Students got enough with the score 2.5, So they can be categorized in good level of speaking ability with the average 3.4%. Viewed from the four aspects of speaking ability test the percentagevocabulary:3.74%,structure: 3.59%, pronounciation: 3.16%, and fluency: 2.92%, the writer conclude that the difficult aspect shown by the students is fluency aspect